Ketamine Reverses Lateral Habenula Neuronal Dysfunction and Behavioral Immobility in the Forced Swim Test Following Maternal Deprivation in Late Adolescent Rats - Shepard, Ryan D.; Langlois, Ludovic D.; Browne, Caroline A.; Berenji, Aylar; Lucki, Irwin; Nugent, Fereshteh S. (Frontiers in Synaptic Neuroscience, 2018)
Mounting evidence suggests that the long-term effects of adverse early life stressors on vulnerability to drug addiction and mood disorders are related to dysfunction of brain monoaminergic signaling in reward circuits. Recently, there has been a growing interest in the lateral habenula (LHb) as LHb dysfunction is unquestionably linked to the development of mental health disorders through monoaminergic dysregulation within brain reward/motivational circuits and thus presents a critical target for novel anti-depressants, such as ketamine. Here, we show that maternal deprivation (MD), a severe 24h early life stressor, increases LHb intrinsic excitability and LHb bursting activity, and is associated with depressive and anxiety-like behavioral abnormalities in young adult male rats. A single in vivo injection of ketamine is sufficient to exert prolonged antidepressant effects through reversal of this early life stress-induced LHb neuronal dysfunction and behavioral despair. Our assessment of ketamine’s long-lasting beneficial effects on reversal of MD-associated changes in LHb neuronal function and behavior highlights the critical role of the LHb in pathophysiology of depression associated with severe early life stress and in response to novel fast-acting antidepressants.